Application of X-Ray Powder Diffraction for Analysis of Selected Dietary Supplements Containing Magnesium and Calcium - Jendrzejewska, Izabela (Frontiers in Chemistry, 2020)
It is estimated that approximately 50% of medications and dietary supplements offered in the Internet are counterfeit. X-ray diffraction is one of the techniques which may be applied successfully to identify various chemical compounds in polycrystalline mixtures such as dietary supplements, but also medications, narcotics or designer drugs. X-ray diffraction enables to learn compositions of such mixtures. For the tests, 22 dietary supplements which should contain magnesium and calcium compounds, available in pharmacies, groceries, Internet shops, as well as in shops for sportspersons, were selected. Identification of crystalline substances present in the tested sample consists in determination of inter-planar distances dhkl of investigated substances and determination of intensity of the obtained diffraction lines, and then in comparing them with values contained in diffraction databases. In this study, the ICDD-PDF2 database was used. The most important criterion in qualitative analysis, confirming the presence of a given phase, is the conformity of positions of diffraction lines in the recorded diffraction image with those in the reference image. Reflex shifts for the individual 2θ angles compared with the data from the database should not exceed 0.2°. In most cases, X-ray analysis of the investigated dietary supplements proved presence of magnesium and calcium compounds declared by the manufacturer, as well as allowed for identifying auxiliary substances present in the tested products. In the case of two magnesium-containing dietary supplements, the magnesium compounds declared by the manufacturer were not found. Our studies confirmed the effectiveness of X-ray structural analysis and proved the possibility to distinguish counterfeit preparations from authentic products, as well as to use this method for quality control of such pharmaceutical preparations.